Factor 36x^3 = (2)(2)(3)(3)(x)(x)(x)
Factor 8x = (2)(2)(2)(x)
Take what they have in common which is (2)(2)(x) and multiply and it will be 4x.
First you had to remove parenthesis first.
![-3*2=-6](https://tex.z-dn.net/?f=-3%2A2%3D-6)
Multiply by the numbers.
![3*2=6](https://tex.z-dn.net/?f=3%2A2%3D6)
Final answer ![\boxed{=-6}](https://tex.z-dn.net/?f=%5Cboxed%7B%3D-6%7D)
![6/3=2](https://tex.z-dn.net/?f=6%2F3%3D2)
![2*3=6](https://tex.z-dn.net/?f=2%2A3%3D6)
![6/2=3](https://tex.z-dn.net/?f=6%2F2%3D3)
Hope this helps!
And thank you for posting your question at here on brainly, and have a great day.
-Charlie
Answer:
The constant rate of change is the average change that happens between a time period. In slope-intercept form, it is the mx part of the equation.
y = mx + b
Answer:The answer is 1 and 3
Step-by-step explanation: